The Effect of Lean Six Sigma Implementation, Information Technology Utilization, and Bed Capacity on Length of Inpatient Stay at Karya Medika Hospital, Bantar Gebang, Bekasi, in 2025 - Gunardi, Astri; Kridawati, Atik; Herawati, Herawati; Marliana, Thika (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
The Length of stay is a crucial indicator in hospital service systems. This study aims to analyze the influence of Lean Six Sigma implementation, the use of information technology, and bed capacity on the length of stay at RS Karya Medika Bantar Gebang. The research method used is a quantitative approach with a descriptive analytical design. Data were collected through questionnaires and analyzed using univariate, bivariate, and multivariate tests. The univariate analysis results show that the majority of respondents are aged 20-35 years (59.00%), female (64.10%), and work as nurses (56.40%). Bivariate analysis using Pearson correlation test shows that Lean Six Sigma implementation has a strong relationship with length of stay (r = 0.855, p = 0.000), the use of information technology has a very strong relationship (r = 0.906, p = 0.000), and bed capacity also has a strong relationship (r = 0.838, p = 0.000). Multivariate analysis results using multiple linear regression indicate that Lean Six Sigma implementation (β = 1.583, p = 0.000) and the use of information technology (β = 0.954, p = 0.043) significantly affect the length of stay, while bed capacity (β = 0.505, p = 0.243) does not have a significant effect. The regression model used has an R value of 0.944 and an R Square value of 0.892, indicating that 89.2% of variations in length of stay can be explained by the three independent variables. The conclusion of this study is that Lean Six Sigma implementation and the use of information technology significantly contribute to reducing the length of stay, while bed capacity does not have a direct impact. Therefore, hospitals are advised to further optimize the implementation of Lean Six Sigma and information technology to improve service efficiency.